2014
DOI: 10.1371/journal.pone.0102942
|View full text |Cite
|
Sign up to set email alerts
|

Tai Chi for Improvement of Motor Function, Balance and Gait in Parkinson's Disease: A Systematic Review and Meta-Analysis

Abstract: BackgroundRecently, several studies assessed the effectiveness of Tai Chi for Parkinson's disease (PD), but the role of Tai Chi in the management of PD remained controversial. Therefore, the purpose of this systematic review is to evaluate the evidence on the efficacy of Tai Chi for PD.MethodsSix English and Chinese electronic databases, up to April 2014, were searched to identify relevant studies. The risk of bias in eligible studies was assessed by Cochrane Collaboration's tools. The primary outcomes were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 31 publications
(103 reference statements)
3
56
3
Order By: Relevance
“…Our subgroup analyses demonstrated the most beneficial effects for exercises incorporating balance components, such as dancing or tai chi. Recently, published meta-analyses specifically investigating the effectiveness of tai chi 18 and dancing 19 on balance in participants with PD presented similar positive results in favor of these types of exercise therapy. Our findings are also in line with results from Allen et al 22 who classified tai chi and dancing as "highly challenging" balance exercise and concluded that these interventions are most beneficial for balance-related activities in participants with PD.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our subgroup analyses demonstrated the most beneficial effects for exercises incorporating balance components, such as dancing or tai chi. Recently, published meta-analyses specifically investigating the effectiveness of tai chi 18 and dancing 19 on balance in participants with PD presented similar positive results in favor of these types of exercise therapy. Our findings are also in line with results from Allen et al 22 who classified tai chi and dancing as "highly challenging" balance exercise and concluded that these interventions are most beneficial for balance-related activities in participants with PD.…”
Section: Discussionmentioning
confidence: 89%
“…However, exercise therapy was not the primary focus in this review and the different types of physical interventions were not analyzed on the basis of their specific content. Other recently published meta-analyses focused on specific types of exercise, showing improvements in measures of postural stability in individuals with PD after performing tai chi, 18 dancing, 19 or aerobic exercises. 20 Furthermore, on the basis of their literature review, Canning et al 21 recommend to promote exercise for falls prevention in persons with PD, especially challenging balance exercises in a supervised setting.…”
Section: Introductionmentioning
confidence: 99%
“…For studies that did include meta-analysis, one in 2014 focused only on Tai Chi (excluding Qigong) and included 9 trials in quantitative synthesis (vs. 15 in the present study) [7]. Another 2014 meta-analysis focused only on motor outcomes and included 8 trials [13]. A 2015 review that evaluated both Tai Chi and Qigong included 13 RCTs, however, 4 of these were published in Chinese and thus are not included in our review [14].…”
Section: Discussionmentioning
confidence: 99%
“…Potentially, effective programs are an Intensive Rehabilitation Program (4 weeks, 5 times a week, combined types of exercise) [78,79], and the Lee Silverman Voice Treatment -BIG program (high amplitude movements, sensory recalibration and self-cueing) [80]. Other types of exercise for which evidence is increasing are Tai Chi [81][82][83], hydrotherapy [84], boxing [85] and dancing [86][87][88]. There is very little evidence for exercise to improve hand function.…”
Section: Exercisementioning
confidence: 99%